Study of morphological, anatomical and Palynological of Characteristics for a plant Mentha longifolia L. and identification Essential oil components. - حداد دينا; بابوجيان جورجيت; صقر هزار (Latakia University Journal -Biological Sciences Series, 2021)
This research deals with determining the morphological and micro-morphological characteristics of Mentha longifolia L., morphological study indicated its small violet flowers meet in roundabouts to form a spike-shaped inflorescence. Its leaves are lanceolate shaped with a serrated margin. The fruit is nutel and oval-shaped (0.6-0.7 mm). It has reticulated coarse decoration on its surface. Its Stomata are (Diacytic). As for the trichomes, they were of two types: the first eglandular with a Conical base and single-celled or multi-celled, full or not filled (fragile).The second type is glandular with two forms; the first peltate gland having (8) cells . The second form is capitate gland consisting of an oval cell and a stalk composed of one or two cells. The anatomical study of the stem showed that it is polygon quadrate and has colanchymatic thicknesses at the corners. The lower epidermis of leaf was richer by secretory cells from the upper. The study of pollen also showed that they are hexagonal (6-colpate, 6-zonocolpate). The pollen shape is spherical to elongated or semi-spherical (prolate-spheroida to sub-prolate). The outer surface ornament (Tectum (is medium coarsely reticulate. The components of the essential oil were determined using a GC/MS. It was found that 16 compounds present 4 of which were the main ones and recorded higher percentages than the rest and the highest Percentage carvone oxide (90.484%), followed by isomenthone (2.94%), thymol (1.75%), respectively. 1,8-cineole (1.537%).